Object-Feature Binding Survives Dynamic Shifts of Spatial Attention - Dowd, Emma Wu (Psychol Sci, 2019)
Visual object perception requires integration of multiple features; spatial attention is thought to be critical to this binding. But attention is rarely static—how does dynamic attention impact object integrity? Here, we manipulated covert spatial attention and had participants (total N = 48) reproduce multiple properties (color, orientation, location) of a target item. Object-feature binding was assessed by applying probabilistic models to the joint distribution of feature errors: Feature reports for the same object could be correlated (and thus bound together) or independent. We found that splitting attention across multiple locations degrades object integrity, whereas rapid shifts of spatial attention maintain bound objects. Moreover, we document a novel attentional phenomenon, wherein participants exhibit unintentional fluctuations—lapses of spatial attention—yet nevertheless preserve object integrity at the wrong location. These findings emphasize the importance of a single focus of spatial attention for object-feature binding, even when that focus is dynamically moving across the visual field.